MODERN LEGAL EDUCATION AND SCIENCE: A CONCEPTUAL VIEW ON REFORMING - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the purpose of the scientific article is to summarize the results of the VII International scientific and practical conference "Modern university law education and science" and to determine the priority tasks of reforming the legal education and scientific activity. Methods: general and special scientific (special) methods were used to achieve the stated goal. The use of these methods allowed to outline the problems of the development of modern university law education and science, to determine the prospects for their development, taking into account world experience. Results: recommendations for use in the reform of law and higher education in Ukraine: in improving the draft law on legal (law) education and universal access to the legal profession for the professional training of a lawyer in accordance with European standards of higher education and the legal profession. The proposals and recommendations made during the conference will help everyone to successfully overcome the problems associated with the difficult period of reform and create all the necessary conditions for the graduate of the university to be ready to enter the globalized world of high competencies and intense competition. Discussion: the authors suggest continually working to improve the quality of legal education in higher education institutions so that the future lawyer could abstractly, logically, critically and creatively think, and generate new ideas. Universities should ensure that students acquire practical skills through the introduction of such disciplines as a legal research laboratory and imitation of the litigation.